Fabrication of poly ( $$ε$$ -caprolactone) 3D scaffolds with controllable porosity using ultrasound - Martin Weber; Dmitry Nikolaev; Mikko Koskenniemi; Jere Hyvönen; Joel Jääskeläinen; Armand Navarre; Ekaterina Takmakova; Arun Teotia; Pekka Katajisto; Robert Luxenhofer; Edward Hæggström; Ari Salmi (Scientific Reports)
Abstract 3D printing has progressed significantly, allowing objects to be produced using a wide variety of materials. Recent advances have employed focused ultrasound in 3D printing, to allow printing inside acoustically transparent materials. Here we introduce a selective ultrasonic melting (SUM) method for 3D printing of poly ( $$ε$$ -caprolactone) powder mixed with water. The printing was done by mechanically moving a focused ultrasound transducer. The microstructure and porosity of the prints were analyzed with micro-computed tomography. The open porosity of the printed samples was determined using the water intrusion method and by passing fluorescent microspheres through the structure. The cytocompatibility of the printed structures was confirmed by seeding NIH-3T3 fibroblast cells on the scaffolds, followed by analysis using live/dead fluorescent assay and visualization using scanning electron microscopy. We demonstrated that SUM is a viable technique to print structures with active control of their porosity. This method provides an alternative to methods such as fused deposition modelling and material jetting.